The Difference in the Effectiveness of Physical Education, Sports and Health Learning during the Covid-19 Quarantine (Media Ilmu Keolahragaan Indonesia, 2022)
Abstract. Covid-19 is a deadly virus that attacks the human respiratory system and can be transmitted through saliva splashes. The Indonesian Ministry of Education issued a circular letter from the Minister of Education and Culture No. 4 of 2020 concerning the Implementation of Policy and Education in the Emergency Period of the Spread of Corona Virus Disease (Covid-19) by dismissing and replacing the Teaching and Learning Activities (KBM) process in schools by using an online system (online). This research is a comparative descriptive study. Research population i.e. all class XI students in high schools and vocational schools throughout the Nogosari district, for high school students totaling 130 students, and vocational students totaling 150 students, so the total sample is 280. Research results indicator learning conditions there are high school students included in the effective category, indicators of learning methods SMA students are included in the quite effective category, indicators of learning outcomes for SMA students are in the quite effective category 2) indicators of learning conditions for SMK students are in the quite effective category, indicators of learning methods for SMK students are in the quite effective category, indicators of learning outcomes for SMK students are in the moderate category effective. Abstract in Indonesia. Covid-19 adalah virus mematikan yang menyerang sistem pernapasan manusia dan dapat menular melalui percikan air liur. Kementerian pendidikan Indonesia mengeluarkan surat edaran mendikbud No. 4 Tahun 2020 tentang Pelaksanaan Kebijakan dan Pendidikan Dalam Masa Darurat Penyebaran Corona Virus Disease (Covid-19) dengan meliburkan dan mengganti proses Kegiatan Belajar Mengajar (KBM) di sekolah dengan menggunakan sistem dalam jaringan (daring. Penelitian ini merupakan penelitian deskriptif komparatif. Populasi penelitian yaitu seluruh siswa kelas XI di SMA dan SMK se–kecamatan Nogosari, untuk siswa SMA berjumlah 130 siswa, dan siswa SMK berjumlah 150 siswa, jadi total sampel 280 siswa. Hasil Penelitian indicator kondisi pembelajaran ada mahasiswa SMA termasuk dalam kategori efektif, indikator metode pembelajaran siswa SMA termasuk dalam kategori cukup efektif, indikator hasil pembelajaran siswa SMA berada pada kategori cukup efektif 2) indikator kondisi pembelajaran pada mahasiswa SMK dalam kategori cukup efektif, indikator metode pembelajaran siswa SMK dalam kategori cukup efektif, indikator hasil pembelajaran siswa SMK berada pada kategori cukup efektif.